Hysteroscopic Evaluation of Chronic Endometritis Incidence in Unexplained Infertile Women with Recurrent Implantation Failure: Six Years Experience - Nur DOKUZEYLÜL GÜNGÖR; Tuğba GÜRBÜZ; Arzu YURCİ (Ahi Evran Medical Journal, 2022)
Purpose: To evaluate histeroscopically-proved chronic endometritis (CE) incidence in unexplained infertility cases with recurrent implantation failure (RIF). Materials and Methods: This cross-sectional retrospective study was done on 529 participants who attended our hospital's infertility clinic from January 2014 to August 2020. The participants were at the age of 18-39 years. We divided the subjects into two groups, i.e., unexplained infertile patients with RIF (Group:1; n:187) and unexplained infertile patients without RIF (Group:2; n:342). Results: The women had a mean age of 31.6 ±5.1 years. Hysteroscopic findings were as follows:14 (2.6%) had chronic endometritis, 19 (3.6%) had polyps, and 496 (93.8%) had no pathological findings. Age, BMI, AMH level, total dose of gonadotropin, duration of stimulation, number of retrieved oocytes, Metaphase II (MII), and Pronucleus (PN) showed no significant difference between the two groups. Also, infertility type (P=0.09) and smoking(P=0.5) were not statistically different between the two groups. In addition, the two groups showed no statistically significant difference in polyps (p=0.8) and CE (p=0.1), while the two groups showed a statistically significant difference in endometrial pathology (p<0.001). Conclusion: In this study, it was shown that those with RIF did not show a higher incidence of CE, but endometrial pathologies were increased in this group of patients. So hysteroscopy should be done in RIF patients with unexplained infertility.